2012
DOI: 10.1002/jbmr.1797
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes and γδ T cells control the acute-phase response to intravenous zoledronate: Insights from a phase IV safety trial

Abstract: Aminobisphosphonates (NBPs) are used widely against excessive bone resorption in osteoporosis and Paget's disease as well as in metastatic bone disease and multiple myeloma. Intravenous NBP administration often causes mild to severe acute-phase responses (APRs) that may require intervention with analgesics and antipyretics and lead to treatment noncompliance and nonadherence. We here undertook a phase IV safety trial in patients with osteoporosis to investigate the APR of otherwise healthy individuals to first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 42 publications
5
59
0
Order By: Relevance
“…In reminiscence of the earlier observation of CD80 upregulation on circulating DCs in zoledronate-treated HIV patients [54], our own clinical trial in otherwise healthy individuals with osteoporosis demonstrated a significant although transient increase in the surface expression of CD14, CD40, CD80, and HLA-DR of circulating CD14 + monocytes after first time treatment with zoledronate [65]. This study also identified pre-treatment levels of monocytes and central/memory Vc9/Vd2 T cells as predictive risk factors for the occurrence of subclinical and clinical symptoms, in support of the interaction of these two cell types in vivo.…”
Section: Differentiation Of Monocytes: Local Generation Of Inflammatomentioning
confidence: 51%
See 3 more Smart Citations
“…In reminiscence of the earlier observation of CD80 upregulation on circulating DCs in zoledronate-treated HIV patients [54], our own clinical trial in otherwise healthy individuals with osteoporosis demonstrated a significant although transient increase in the surface expression of CD14, CD40, CD80, and HLA-DR of circulating CD14 + monocytes after first time treatment with zoledronate [65]. This study also identified pre-treatment levels of monocytes and central/memory Vc9/Vd2 T cells as predictive risk factors for the occurrence of subclinical and clinical symptoms, in support of the interaction of these two cell types in vivo.…”
Section: Differentiation Of Monocytes: Local Generation Of Inflammatomentioning
confidence: 51%
“…Monocytes are critical for the activation and proliferation of Vc9/Vd2 T cells in response to neutrophil-released microbial compounds [9,10], and are thus likely to drive early inflammatory responses in acute microbial infections [60], which can be mimicked in vitro by providing soluble HMB-PP [61,62]. In addition, monocytes are also essential for Vc9/Vd2 T cell responses to aminobisphosphonates such as zoledronate by facilitating uptake of these compounds through endocytosis and intracellular accumulation of IPP [63][64][65]. However, only a few studies have examined the feedback of activated Vc9/Vd2 T cells on monocytes.…”
Section: Differentiation Of Monocytes: Local Generation Of Inflammatomentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical benefit may in fact stem, at least in part, from the activity of zoledronate on the patient's immune system by specifically stimulating V␥9/V␦2 T cells, which compose 0.5%-5% of circulating T cells in healthy adults [5]. Targeted immunotherapy studies directly exploiting the potent non-major histocompatibility complexrestricted cytotoxicity of V␥9/V␦2 T cells have shown excellent safety profiles and promising clinical observations in a variety of hematological and solid cancers [6], including metastatic breast cancer [7].Studies by us and others have demonstrated that zoledronate treatment induces a rapid and long-lasting conversion of the peripheral V␥9/V␦2 T-cell phenotype from CD27 ϩ CD45RA Ϫ central memory T (T CM ) cells to CD27 Ϫ CD45RA Ϫ effector memory T (T EM ) cells in many, but not all, individuals [7][8][9]. In Figure 1, zoledronate-treated breast cancer patients with stable disease showed elevated proportions of V␥9/V␦2 T EM cells at the time of blood sampling compared with patients with progressing disease and untreated controls (Fig.…”
mentioning
confidence: 99%